Analysis of Mathematic Critical Thinking Abilities of 4th Class Primary School Students on Fraction Material as well as Gender Differences - Aulia, Syafira Nur Azmi; Sutarni, Sri (FKIP Universitas Muhammadiyah Tangerang, 2024)
The purpose of this study was to assess the mathematical critical thinking abilities of fourth-grade elementary school students. The research was conducted on a sample of students from class IVB at SD Negeri 1 Gatak, who were given a written test consisting of 4 questions on equivalent fractions to evaluate their mathematical critical thinking abilities. The study was titled